T‐cell receptor repertoire analysis for the diagnosis and treatment of solid tumor: A methodology and clinical applications. Issue 10 (17th July 2020) - Li, Na; Yuan, Jiani; Tian, Wenjia; Meng, Lin; Liu, Yongyu
Abstract: T cells, which are involved in adaptive immunity, are essential in the elimination of tumor cells. Mature T cells can specifically recognize the antigen on the major histocompatibility complex (MHC) molecule through T‐cell receptors (TCR). The unique rearrangement mechanisms during T‐cell maturation provide great diversity to TCR, ensuring specific recognition between T cells and antigens. Thus, TCR repertoire analysis occupied an important position in T‐cell regarding research. Nowadays, next‐generation sequencing technology allows the simultaneous detection of TCR sequences with high throughput, and several evaluation indexes facilitate the measure of TCR repertoire. Based on this new methodology, discoveries are made across a range of tumor types. Results have shed light on the TCR repertoire differences between cancer patients and healthy control as well as between individual's lesions, paracancer, and peripheral blood samples. The potential of TCR repertoire as a biomarker for immunotherapy efficacy is also widely studied as TCR repertoire represents different baseline within individuals and shows dynamic change during treatment. Accurate delineation of the T‐cell repertoire can further the understanding of the immune system response to tumorigenesis. Still, existing researches are insufficient to clarify the specific clinical implications of TCR dynamic change and the definite role of TCR repertoire diversity during the treatment process. The results of some studies are even contrary. In this article, we reviewed TCR rearrangement mechanisms and analysis methods. Recent progress of TCR sequencing technology in tumor research is also discussed. In conclusion, intensive studies over an extended range of cancer types and a broadened group of subjects should be carried to solidify the TCR repertoire's position as an immunotherapy biomarker.